Cross sectional geometries effect on the energy efficiency of a photovoltaic thermal module: Numerical simulation and experimental validation. (15th October 2020) - Pang, Wei; Zhang, Yongzhe; Duck, Benjamin C.; Yu, Hongwen; Song, Xuemei; Yan, Hui
Abstract: The operating temperature influences both the electrical efficiency and thermal efficiency of a photovoltaic thermal (PVT) module. In this paper, a simplified thermal transfer model is used to search for the optimal structure of a high efficiency PVT module. For an aluminum collector with a given thickness, the optimal ratio between size and spacing and cross sectional geometry of the flow channels has been found with numerical simulations using computational fluid dynamics (CFD). The temperature distribution of the PVT module constructed with an aluminum collector is found to be more uniform than the conventional sheet-tube PVT module, due to using an improved thermal transfer mode based on the surface contact. To evaluate the impact of cross sectional geometry, the operating temperatures, electrical and thermal efficiencies of two PVT modules designed with rectangle and arch geometries are examined under outdoor conditions. Measured experimental intercept values of instantaneous thermal efficiencies are close to simulation results, demonstrating the utility of the approach as a reference for a new generation of PVT modules in future. Highlights: An effect of cross sectional geometries on the performance of the PVT module was investigated. An optimal structure of the PVT module was provided by ratios of Si: Sp. Good agreement presented in temperatures between numerical and experimental results.